2012
DOI: 10.1007/s00330-012-2619-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of multi-contrast 7-T MR imaging in multiple sclerosis: increased lesion detection compared to 3 T confined to grey matter

Abstract: Using a clinical multi-contrast MRI protocol, increased lesion detection was observed in cortical GM but not in WM. Given the clinical relevance of GM abnormalities, this may have consequences for clinical outcome measures, prognostic classification and future diagnostic criteria incorporating GM abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 39 publications
1
52
0
6
Order By: Relevance
“…For T1 and FLAIR, this was even 91% and 238%, respectively. 26 Another study found a 65% increase in cortical lesion detection with 7T T2*WI versus 3T DIR. 10 The same research group also investigated how various lesion types contributed to physical and cognitive performance.…”
Section: Discussionmentioning
confidence: 97%
“…For T1 and FLAIR, this was even 91% and 238%, respectively. 26 Another study found a 65% increase in cortical lesion detection with 7T T2*WI versus 3T DIR. 10 The same research group also investigated how various lesion types contributed to physical and cognitive performance.…”
Section: Discussionmentioning
confidence: 97%
“…However, these techniques have low sensitivity for the heterogeneous pathologic substrate of individual lesions. Although a recent study [107] compared T 1 WI, T 2 WI and FLAIR at both 3T and 7T, these techniques did not appear to increase sensitivity for detection of WM lesions. On the other hand, 3D--FLAIR at 7T could be tailored to improve sensitivity in depicting grey matter lesions [107].…”
Section: Inversion Recoverymentioning
confidence: 89%
“…Additional pulse sequences such as the double inversions recovery (DIR) and the phase sensitive inversion recovery (PSIR) sequences have improved the detection rate of cortical GM lesions and the sensitivity can be even further increased by applying these pulse sequences at higher magnetic field strengths (Fig. 4) [20,21]. However, it has been shown that the sensitivity of MRI using a dedicated protocol for grey matter detection of disease activity (or its absence) by MRI in a patient that receives an immunomodulatory treatment represents a measure of treatment response.…”
Section: New Mri Markers and Techniques For Ms Diagnosismentioning
confidence: 99%